Formation and stability of green and low-cost magnetoliposomes of the soy lecithin, stigmasterol, and β-sitosterol for hyperthermia treatments - Rosangela Maria Ferreira da Costa e Silva; Ângela Leão Andrade; Erico Tadeu Fraga Freitas; Thalita Marcolan Valverde; Luciano Roni Silva Lara; Darliane Aparecida Martins; Jorge Luis Lopez; Humberto Osório Stumpf; Clésia Cristina Nascentes; Alfredo Miranda de Goes; Rosana Zacarias Domingues (Scientific Reports)
Abstract Magnetoliposomes containing magnetite, soy lecithin, stigmasterol, and beta-sitosterol of the mean size minor than 160 nm were obtained by a scalable and green process using autoclave and sonication without organic solvents. The formation, size of the liposome, linkage, and encapsulation of the magnetite were evaluated by Cryo-TEM. The stability of magnetoliposomes after storage for 6 months at 4 °C was improved by liposome size, the ability of soy lecithin to preserve the magnetite phase against oxidation, pH, polydispersity index, and zeta potential. The iron oxide phase stability was assessed using no conventional X-ray diffraction (high-resolution transmission electron microscopy), energy loss electron spectroscopy, and selected area electron diffraction) in time zero (fresh sample) and 6 months. The high zeta potential measured for magnetoliposomes, │53│ mV, indicated a low tendency to agglomerate. Lip-Fe3O4@lecithin with concentrations of 0.58 mg mL−1 of liposome showed high cell viability and are potential candidates for drug delivery and hyperthermia treatments in 3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide (MTT) assays.